Amyloid imaging for cognitive studies in cohorts with racial and ethnic diversity: Neuroimaging / imaging and genetics. (7th December 2020) - Sano, Mary; Zhu, Carolyn W; Aloysi, Amy; Grossman, Hillel; Loizos, Maria; Hedden, Trey; Kinsella, Michael T; Neugroschl, Judith
Abstract: Background: To compare rates of amyloid positivity in non‐Hispanic whites with diverse cohorts including Hispanic, Black, Asian, and other research participants. Methods: Participants were enrolled in the ADRC, completed the Unified Data Set (UDS) and underwent amyloid imaging (2011‐2019). Racial and ethnic origin was self‐reported. Referral source and study enrollment were recorded. Amyloid images received a clinical read by a neuro‐radiologist who was blinded to patient characteristics used to determine amyloid status, regardless of study‐specific amyloid determination. Results: 191 cases who had received amyloid imaging were identified. 113 were non‐Hispanic white and 78 were minorities (36 non‐Hispanic Black, 28 Hispanic, 6 Asian, 8 other). Aside from the most common referral source from physicians (42%) for participants in both white and minority groups (42%), referral sources differed between white and minority participants. Amyloid imaging was performed using Amyvid (florbetapir F18 injection, n=94) and Neuraceq (florbetaben F18, n=97, 50.8%) tracers but usage differed between white and minority groups. Participant characteristics were: mean age 68.1 (SD=10.8) at time of scan, 52.9% male, mean CDR Sum of Boxes 0.8 (SD=1.3), 57.9% had no Apolipoprotein e4 alleles. Differences in these measures were not statistically significant between white and minority groups. Education (16.7±2.5 vs. 15.0±3.3) and cognitive composite scores (5.0±1.8 vs. 4.5±1.4) were higher in white compared to minority group (both p<0.01). Amyloid positivity was 27.4% (31/113) in whites, significantly higher than 9.0% (7/78) among minorities (p=0.002). Both groups demonstrated increasing amyloid positivity with age with whites ranging from 11.8% in those younger than 70, 34.0% in those age 70‐79, to 66.7 % in those 80 or older, and ranging from 4.7%, 14.3%, 14.3% in minorities in the same age groups, respectively. Results from analysis restricted to those with a UDS determined diagnosis of normal cognition, aMCI or AD remained the same. Conclusions: In this relatively small convenience sample from diverse sources of recruitment and differential use of tracers for imaging studies we confirm previous impressions of lower rates of amyloid positivity in aging minority cohorts despite poorer cognitive performance. Both white and minority cohorts demonstrated age related increase in the presence of brain amyloid positivity.